Velocity response of Petermann Glacier, northwest Greenland, to past and future calving events. - Hill, E.A.; Hilmar Gudmundsson, G.; Carr, R.J.; Stokes, C.R. (The Cryosphere, 2018)
Dynamic ice discharge from outlet glaciers across the Greenland ice sheet has increased since the beginning of the 21st century. Calving from floating ice tongues that buttress these outlets can accelerate ice flow and discharge of grounded ice. However, little is known about the dynamic impact of ice tongue loss in Greenland compared to ice shelf collapse in Antarctica. The rapidly flowing (∼1000ma−1) Petermann Glacier in north-west Greenland has one of the ice sheet's last remaining ice tongues, but it lost ∼50–60% (∼40km in length) of this tongue via two large calving events in 2010 and 2012. The glacier showed a limited velocity response to these calving events, but it is unclear how sensitive it is to future ice tongue loss. Here, we use an ice flow model (Úa) to assess the instantaneous velocity response of Petermann Glacier to past and future calving events. Our results confirm that the glacier was dynamically insensitive to large calving events in 2010 and 2012 (<10% annual acceleration). We then simulate the future loss of similar sized sections to the 2012 calving event (∼8km long) of the ice tongue back to the grounding line. We conclude that thin, soft sections of the ice tongue >12km away from the grounding line, provide little frontal buttressing, and removing them is unlikely to significantly increase ice velocity or discharge. However, once calving removes ice within 12km of the grounding line, loss of these thicker and stiffer sections of ice tongue could perturb stresses at the grounding line enough to substantially increase inland flow speeds (∼900ma−1), grounded ice discharge, and Petermann Glacier’s contribution to global sea level rise.